2015
DOI: 10.1016/j.asr.2015.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Where does the Thermospheric Ionospheric GEospheric Research (TIGER) Program go?

Abstract: International audienceAt the 10th Thermospheric Ionospheric GEospheric Research (TIGER/COSPAR) symposium held in Moscow in 2014 the achievements from the start of TIGER in 1998 were summarized. During that period, great progress was made in measuring, understanding, and modeling the highly variable UV-Soft X-ray (XUV) solar spectral irradiance (SSI), and its effects on the upper atmosphere. However, after more than 50 years of work the radiometric accuracy of SSI observation is still an issue and requires furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…The interaction of solar radiation with the ionosphere is complicated due to several mechanisms with the potential to modulate the thermosphere-ionosphere (T-I) system at different timescales ranging from the 11-year solar cycle down to minutes (e.g., Liu et al, 2003;Afraimovich et al, 2008;Liu and Chen, 2009;Chen et al, 2012). The ionosphere plasma response to solar EUV and UV variations has been widely studied using ground-and space-based observations (e.g., Jakowski et al, 1991;Jacobi et al, 2016;Schmölter et al, 2018;Jakowski et al, 1999), as well as by numerical and empirical modeling (e.g., Ren et al, 2018;Vaishnav et al, 2018a, b). These studies have shown that the response of the ionosphere to solar EUV radiation variations is delayed by 1-2 d at the 27 d solar rotation period (e.g., Jakowski et al, 1991;Afraimovich et al, 2008;Jakowski et al, 2002;Min et al, 2009;Jacobi et al, 2016;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of solar radiation with the ionosphere is complicated due to several mechanisms with the potential to modulate the thermosphere-ionosphere (T-I) system at different timescales ranging from the 11-year solar cycle down to minutes (e.g., Liu et al, 2003;Afraimovich et al, 2008;Liu and Chen, 2009;Chen et al, 2012). The ionosphere plasma response to solar EUV and UV variations has been widely studied using ground-and space-based observations (e.g., Jakowski et al, 1991;Jacobi et al, 2016;Schmölter et al, 2018;Jakowski et al, 1999), as well as by numerical and empirical modeling (e.g., Ren et al, 2018;Vaishnav et al, 2018a, b). These studies have shown that the response of the ionosphere to solar EUV radiation variations is delayed by 1-2 d at the 27 d solar rotation period (e.g., Jakowski et al, 1991;Afraimovich et al, 2008;Jakowski et al, 2002;Min et al, 2009;Jacobi et al, 2016;Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The ultraviolet, and particularly EUV, irradiance is intrinsically linked to solar cycle magnetic variation, and so is the galactic cosmic ray flux, which is again exhibiting record highs, as it did prior to solar cycle #24 (e.g., http://neutronm.bartol.udel.edu). Whether this serves as a bellwether for broader solar changes may be discoverable by the ongoing program of comprehensive space‐based observations of total and spectral solar irradiance (e.g., Dudok de Wit et al, ; Haberreiter et al, ; Schmidtke et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Why was it necessary to take into account the microwave fluxes from the ionosphere? The fact is that in numerous space experiments, by now, the efforts of world science have determined the variations of all energy flows associated with solar and geomagnetic activity [30,31]. The results obtained indicate that these flows do not reach the lower atmosphere and, therefore, the direct impact of the effects of solar flares and magnetic storms on the biosphere and the lower layers of the atmosphere (the troposphere and its weather and climate char-acteristics) is impossible.…”
Section: Associate Formation In Aqueous Biosolutions Under Microwave ...mentioning
confidence: 99%